2012
DOI: 10.1016/j.juro.2012.02.2568
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Calculi Detection Using Low Dose Computerized Tomography Protocols is Compromised in Overweight and Underweight Patients

Abstract: The sensitivity and specificity for the detection of ureteral calculi on computerized tomography were decreased for underweight and overweight subjects when using extremely low dose radiation settings (less than 1 mSv). Low dose protocols of 15 mAs (2 mSv) can still be used for these subjects without jeopardizing the ability to identify ureteral stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…[12][13][14] These studies have also often excluded or found poor performance of nonsize-adjusted protocols in more obese patients, who are at increased risk for kidney stone and incur a higher radiation dose. 1,[15][16][17][18] Previous studies have also not followed patients receiving reduced-dose CT to determine its ability to predict outcomes and need for intervention.…”
Section: Background and Importancementioning
confidence: 99%
“…[12][13][14] These studies have also often excluded or found poor performance of nonsize-adjusted protocols in more obese patients, who are at increased risk for kidney stone and incur a higher radiation dose. 1,[15][16][17][18] Previous studies have also not followed patients receiving reduced-dose CT to determine its ability to predict outcomes and need for intervention.…”
Section: Background and Importancementioning
confidence: 99%
“…Interestingly, a more recent cadaveric simulation study carried out by Heldt et al . [29] using 3 cadavers of increasing weight/BMI found that although increasing adiposity negatively affected the diagnostic accuracy of ultra-low dose CT (<1 mSv) in detecting ureteral calculi, the sensitivity and specificity of ultra-low dose CT for detecting ureteral calculi was also decreased in underweight cadavers; presumably due to a lack of perinephric and peri-ureteral fat to help delineate the ureters from surrounding structures. However, there was no significant difference in sensitivity and/or specificity at radiation doses of 2 mSv or more, which would still constitute a “low-dose” scan using our definition.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of low-dose CT imaging (2-3.5 mSv) has been thoroughly investigated [17,[31][32][33][34][35]. These studies have consistently shown that low-dose CT provides a sensitivity and specificity >95 % and is similar to conventional CT for the detection of both renal and ureteral calculi [31,36,37].…”
Section: Reducing Radiation During Work-up For Urolithiasismentioning
confidence: 99%
“…Similarly, very thin and very obese patients are better imaged with low-dose, not ultra lowdose imaging, as image noise can impair image clarity [32]. Finally, patients with spinal hardware, reservoirs, hip replacements, or other implants may produce image noise that compromises the radiologic detection of calculi in the corresponding areas with both low and ultra low-dose CT techniques.…”
Section: Reducing Radiation During Work-up For Urolithiasismentioning
confidence: 99%